POLA ASUH ORANG TUA DALAM MENDIDIK ANAK USIA PRASEKOLAH DITINJAU DARI ASPEK BUDAYA LAMPUNG - Fitria, Nita (STKIP Muhammadiyah Pringsewu, 2016)
Culture values have big effort toward individual mind set. In family life, there is a culturein educate their children that need their parentsâ thoughtfulness and control in childhooddevelopment stages. Individual character building started from parenting thatimplemented on their children by their parents. The objective of this research explainedabout parenting profile of lampungnese in educate pre-school children. Method of thisresearch was qualitative descriptive. The data were taken by interview includedobservation and document data (triangulation). The result shown that Lampungneseparents had authoritative parenting character. This fact is relevant to Lampungnesecharacter such as firm and dominant.Keywords: Pola Asuh, Anak Prasekolah, Budaya.